(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Gym has been more popular in recent years since it aids in the maintenance of one’s health, increases flexibility, improves concentration, and motivates individuals to live a healthy and tranquil life. People used to practice Gym on any surface, but today they prefer to do it on a Gym mat since it offers greater comfort and ease. The primary purpose of a Gym mat is to prevent or minimize hand and foot slippage. The Gym mats that have been created so far are not automated and cannot be controlled using a speech system. The researcher suggested an automated mat that can be controlled via a speech system in this article. Temperature sensor, weight sensor, movement sensor, piezoresistive sensor, pressure sensor, vibrator, display screen, roller with direct current (DC) motor, voice system, AI camera, and AI-based controller are all included in this mat. This Gym mat is superior to the previous one since it is automated and can recommend workouts based on the user’s age. The automated Gym mat has a promising future since it may be further customized by incorporating new technologies and mechanics.